Effect of Transcranial Electrical Stimulation over the Posterior Parietal Cortex on Tactile Spatial Discrimination Performance. (1st July 2022) - Saito, Kei; Otsuru, Naofumi; Inukai, Yasuto; Kojima, Sho; Miyaguchi, Shota; Nagasaka, Kazuaki; Onishi, Hideaki
Highlights: Delivering tRNS over the right PPC improved GOT discrimination. Applying tRNS over the left PPC reduced GOT in individuals with a high basal GOT performance. Performing anodal tPCS over the PPC unaltered GOT discrimination. Abstract: The intraparietal sulcus region, which is part of the posterior parietal cortex (PPC), has been shown to play an important role in discriminating object shapes using the fingers. Transcranial random noise stimulation (tRNS) and anodal transcranial pulsed current stimulation (tPCS) are noninvasive strategies widely used to modulate neural activity in cortical regions. Therefore, we investigated the effects of tRNS and anodal tPCS applied to left or right PPC on the tactile discrimination performance of the right index finger in 20 neurologically healthy subjects. A grating orientation task (GOT) was performed before and immediately after delivering tRNS (stimulus frequency 0.1–640 Hz) in Experiment 1 or anodal tPCS (pulse width 50 ms and inter-pulse interval 5 ms) in Experiment 2. Performing tRNS over the right PPC significantly improved discrimination performance on the GOT. Subjects were classified into low and high baseline performance groups. Conducting tRNS over the left PPC significantly reduced the GOT discrimination performance in the high-performance group. By contrast, anodal tPCS delivered to the PPC of the left and right hemispheres had no significant effect on the tactile GOT discrimination performance of the right hand. We show that transcranial electric stimulation over the PPC may improve tactile perception but the effect depends on stimulus modality, parameters, and on the stimulated hemisphere.